Designing the implementation of a quality management system in the Republican Medical Library-Information Centre, Tatarstan, Kazan (Journal of EAHIL, 2016)
The question of a quality management system implementation as a method of quality control improvement of a medical library and information centre is examined in this article. The article describes the introduction of a process approach to management and its successful introduction in the Republican Medical Library-Information Centre of the Republic of Tatarstan, Russian Federation.